Morphology, the bioactive compound and essential oil profiles of Indonesian Syzygium myrtifolium leaf: A brief literature review: - - Jatmiko Eko Witoyo; Nelsy Dian Permatasari; Atika Hamaisa; Panggulu Ahmad Ramadhani Utoro (Journal of Food and Agricultural Product, 2026)
Syzygium myrtifolium leaves are plants commonly found in Indonesia and have the potential to be a source of bioactive compounds and essential oils. This article provides a brief review of the morphological characteristics, bioactive compounds, and essential oil profiles of Syzygium myrtifolium leaves from Indonesia, based on relevant scientific publications. The research method employed was a literature review of journal articles, proceedings, and bachelor’s thesis published between 2015 and 2025, retrieved from Google Scholar, ResearchGate, and Crossref. The study showed that Syzygium myrtifolium leaves have distinctive morphological characteristics, particularly changes in leaf color associated with leaf maturity. Syzygium myrtifolium leaves are reported to contain various bioactive compounds, including flavonoids, phenolics, tannins, saponins, alkaloids, steroids, and triterpenoids. Furthermore, Syzygium myrtifolium leaves produce essential oils with varying yields and volatile compound compositions. Overall, this brief literature review shows the potential of Indonesian Syzygium myrtifolium leaves as a source of bioactive compounds and essential oils for the development of products based on local resources. Keywords: bioactive compounds, essential oil, leaf morphology, Syzygium myrtifolium